2002
DOI: 10.1148/radiol.2252011763
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Open versus Antireflux Stents for Palliation of Distal Esophageal Carcinoma and Prevention of Symptomatic Gastroesophageal Reflux

Abstract: This antireflux stent is as safe and effective as the standard open stent in relieving malignant dysphagia and was successful in reducing symptomatic gastroesophageal reflux.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0
6

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(81 citation statements)
references
References 36 publications
4
71
0
6
Order By: Relevance
“…Stricture at the gastroesophageal junction is amenable to stent insertion with a high rate of technical and clinical success. But severe reflux and aspiration might happen, and a one-way flap valve on the gastric side of the stent could prevent those complications [6][7][8] . Insertion of a metallic stent in the proximal esophageal lesion is technically difficult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stricture at the gastroesophageal junction is amenable to stent insertion with a high rate of technical and clinical success. But severe reflux and aspiration might happen, and a one-way flap valve on the gastric side of the stent could prevent those complications [6][7][8] . Insertion of a metallic stent in the proximal esophageal lesion is technically difficult.…”
Section: Discussionmentioning
confidence: 99%
“…A coated stent placement may prevent tumor ingrowth, but cannot prevent overgrowth of tumors and benign hyperplasic tissues at the edge of stents, but a secondary stent insertion may solve this problem. With stents confined, the risk of perforation and bleeding was low, and ELT or electrocautery might be another good choice [7] . Placement of esophageal metallic stent could lead to many complications.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that the anti-reflux stent was effective in preventing gastro-esophageal reflux [35]. A randomized study comparing this type of anti-reflux stent (25 patients) with a standard open Flamingo Wallstent (25 patients) showed that 3/25 (12%) versus 24/25 (96%) patients, respectively, reported symptoms of gastro-esophageal reflux (P < 0.001), whereas no differences in dysphagia improvement, complications, or reintervention rate were found [34]. Do and colleagues designed a different type of anti-reflux stent with a reflux valve consisting of three leaflets, like a tricuspid valve of the heart instead of the ''windsock-type'' valve.…”
Section: Consmentioning
confidence: 96%
“…Эти результаты были подтвержде-ны в исследовании H-U Laasch и соавт. [12], в кото-ром у 3 (12%) пациентов из 25 с установленным в зону кардии антирефлюксным Z-стентом был выра-женный рефлюкс по сравнению с 24 (96%) пациен-Рис. 3.…”
Section: рис 2 выполнение эндоскопического стентирования пищеводаunclassified